GPS 이중주파수 관측자료를 이용한 전처리 알고리즘 - 김현호; 하지현; 김영국; 림형진; 박관동; Hyun-Ho Kim; Jihyun Ha; Yeong-Guk Kim; Hyung-Jin Rim; Kwan-Dong Park (Journal of Positioning, Navigation, and Timing, 2025)
Inha University and PP-Solution Inc. have been developing the Kinematic Position and Precision Orbit Provider (KPOP) as domestic software for Precise Orbit Determination (POD) for the Global Navigation Satellite System (GNSS) since 2023. As of May 2025, the development of the first version of KPOP is in the POD performance verification stage and this version is equipped with GPS-only POD technology. In general, a GNSS data pre-processing technique is required to improve POD performance. KPOP is applied with detection and repair technology for clock jump and cycle slip. In this paper, we introduce the clock jump and cycle slip detection and repair techniques applied to KPOP and analyze the results of the developed preprocessing algorithms. For the results analysis, GNSS data generated by Inha University and IGS permanent observatories were used, and the results of quality checking programs developed by overseas organizations such as the G-Nut/Anubis and the RINGO were compared. From the results, the detection and repair success ratio of clock jump and cycle slip was in a range of 86-92%, and the data processing time was two seconds for 24-hour observations with a 30-second epoch. These results show that the performance of the KPOP pre-processing algorithm is similar to that of RINGO and G-Nut/Anubis.